Publisher Correction: Livestock husbandry in Islamic Cártama, Málaga, Spain: The micro and bioarchaeology of an open-air Fumier sequence - Rowena Y. Banerjea; Mónica Alonso Eguiluz; Lionello F. Morandi; Jérôme Ros; Luc Vrydaghs; Yannick Devos; Marie Larrieu; Nicolás Losilla; Irene Bertelli; Erika Ribechini; Ana Medina Cuesta; Marcos García García; et al. (Archaeological and Anthropological Sciences, 2026)

Livestock husbandry in Islamic Cártama, Málaga, Spain: the micro and bioarchaeology of an open-air Fumier sequence - Rowena Y. Banerjea; Mónica Alonso Eguiluz; Lionello F. Morandi; Jérôme Ros; Luc Vrydaghs; Yannick Devos; Marie Larrieu; Nicolás Losilla; Irene Bertelli; Erika Ribechini; Ana Medina Cuesta; Marcos García García; et al. (Archaeological and Anthropological Sciences, 2025)
Multidisciplinary micro- and bioarchaeological analyses of late medieval deposits from suburban Cártama, Málaga, Spain, have, for the first time, confidently identified open air fumier deposits, which are supported by preliminary analysis of the faunal assemblage. This demonstrates that Andalusi livestock husbandry practices included periodically burning animal dung within corrals and pens, which is a long-standing practice in the Mediterranean region also observed in prehistoric transhumance. These techniques have commonly been applied to prehistoric fumier or pastoral sites and now demonstrate the importance of expanding micro- and bioarchaeological work to fumier sequences from other periods. This research from Cártama offers a window into the so-called medieval “Green Revolution” associated with Arab migrations and highlights the necessity of identifying in situ penning deposits on archaeological sites and of applying high resolution analyses to examine them. The analyses reveal data on animal feeds, including pearl millet ( Pennisetum glaucum ) and sorghum ( Sorghum bicolor ) which are rare in the Iberian Peninsula at this time, the use of plant resources in livestock husbandry, and the preparation of fertiliser, which are central to understanding farming practices in Al-Andalus.

The zooarchaeological identification of a ‘Morisco’ community after the Christian conquest of Granada (Spain, early 16th century): sociocultural continuities and economic innovations - Marcos García-García; Guillermo García-Contreras; Michelle M. Alexander; Rowena Y. Banerjea; Aleks Pluskowski (Archaeological and Anthropological Sciences, 2021)
This article presents the results of the zooarchaeological analysis of an assemblage dating to the second quarter of the 16th century that was discovered on the current university campus of Cartuja, on the outskirts of Granada (Andalusia, Spain). During the Middle Ages, this area was largely used for agricultural purposes, including as estates owned by high officials of the Nasrid dynasty, the last Islamicate polity in the Iberian Peninsula. The Castilian conquest of Granada in 1492 brought significant changes to the area, with the construction of a Carthusian monastery and the transformation of the surrounding landscape, including changes in property structures, different agrarian regimes and the demolition of pre-existing structures. Among these transformations was the filling up of a well with construction materials, and its further use as a rubbish dump. This fill yielded an interesting and unique zooarchaeological assemblage, the study of which is presented here. The results advance our understanding of changing patterns in animal consumption during the formative transition from the Middle Ages to the Early Modern period at the heart of the former Nasrid Kingdom of Granada, and indicate the continuity of some Andalusi consumption patterns along with specialised production and distribution systems of meat products that have no archaeological precedent in the region, suggesting that the bones were dumped by a possible ‘Morisco’ community (autochthonous Muslims forced to convert to Christianity in 1502).